15.1: Data‐Glasses for Improved User Interaction in 3D. Issue 1 (June 2015) - Herold, Rigo; Weidenmüller, Falk; Penzel, Markus; Ebert, Matthias
Abstract : A problem of state of the art data‐glasses is the fixed distance from the user's eyes to the virtual projection. In the most use cases the user gets the virtual information at the wrong distance. This paper discusses new technical approaches to solve this problem.